2017
DOI: 10.7860/jcdr/2017/25625.9521
|View full text |Cite
|
Sign up to set email alerts
|

HER2/neu Testing In 432 Consecutive Breast Cancer Cases using FISH and IHC - A Comparative Study

Abstract: Introduction: The development of trastuzumab, a HER-2/ neu targeted monoclonal antibody resulted in significant improvements in clinical response and survival in HER-2/neu gene amplified group of patients. Thus, accurate assessment of HER-2/neu status becomes critical. Fluorescence In Situ Hybridization (FISH) and Immunohistochemistry (IHC) are the most commonly used methods for this purpose and specific recommendations exist with regard to the concordance to be observed between the two tests.Aim: Here, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
3
5
1
Order By: Relevance
“…Expression of estrogen receptors was seen in 279 (62.27%) cases in this study, and the expression of progesterone receptors was seen in 304 (67.85%) cases. This is in agreement with Eswarachary V et al, where approximately two thirds (284/432, 65.74%) of their cases were positive for ER receptor expression whereas 59.72% (258/432) of the cases were positive for PR receptor expression [29]. The same results were obtained by Alwan N et al, showing the registered rates of positive ER and PR tumour contents of 67.8% and 65.3% respectively [31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Expression of estrogen receptors was seen in 279 (62.27%) cases in this study, and the expression of progesterone receptors was seen in 304 (67.85%) cases. This is in agreement with Eswarachary V et al, where approximately two thirds (284/432, 65.74%) of their cases were positive for ER receptor expression whereas 59.72% (258/432) of the cases were positive for PR receptor expression [29]. The same results were obtained by Alwan N et al, showing the registered rates of positive ER and PR tumour contents of 67.8% and 65.3% respectively [31].…”
Section: Discussionsupporting
confidence: 89%
“…These figures differ from that reported in other studies like Eswarachary V et al, that showed approximately a third of the cases (143/432, 33.10%) being positive (3+ reactivity) while 47 cases (10.88%) were negative (0, 1+ reactivity) with a substantial number of cases (242/432; 56.01%) showed equivocal positivity (2+ reactivity) [29]. In Varga Z et al, study, 12% of the cases were 3+ on IHC (184 of 1522 cases), 26.5% of the cases were 2+ (404 of 1522), and 61.4% of the cases were negative 0/1+ on IHC (934 of 1522) [30].…”
Section: Discussioncontrasting
confidence: 80%
“…8,14 In some studies, proportion of Her-2/neu amplified cases was reported as 28.8%, 46.29% and 44.9%. 3,23,24 Reports of Her-2/neu gene amplification 74% and 91, 8,14 which is similar to these findings.…”
Section: Discussionsupporting
confidence: 81%
“…We reported on four patients with HER2 IHC3+ with HER2 FISH‐negative tumor samples. Although this is unusual, it is known from comparative studies that this may occur . Recently, preliminary data for 45 patients with HER2‐positive advanced unresectable SGC (of the ductal subtype) treated with docetaxel and trastuzumab in a phase 2 trial showed promising results, that is, overall response rate of 69%, median PFS of 11.3 months and median OS of 38.0 months .…”
Section: Discussionmentioning
confidence: 99%